2008
DOI: 10.1080/09553000802078412
|View full text |Cite
|
Sign up to set email alerts
|

mBAND analysis of chromosome aberrations in lymphocytes exposedin vitroto α-particles and γ-rays

Abstract: This study has confirmed that exchanges induced by exposure to high linear energy transfer (LET) alpha-particle radiation comprise a greater proportion of intrachanges than those induced by exposure to low LET gamma-rays. However, since the majority of these are associated with complex rearrangements and likely to be non-transmissible, this limits their applicability as a marker of past in vivo exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In vitro studies on the induction of chromosome aberrations by a-particle radiation have revealed the complexity of the damage (Anderson et al 2000;Moquet et al 2001;Anderson et al 2002Anderson et al , 2003Barquinero et al 2004;Anderson et al 2007;Tawn et al 2007Tawn et al , 2008Curwen et al 2012). A densely ionizing a-particle will only intersect a small fraction of the cell volume and the deposition of energy and resulting DNA damage will be localized along the particle track, resulting in multiple rearrangements.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In vitro studies on the induction of chromosome aberrations by a-particle radiation have revealed the complexity of the damage (Anderson et al 2000;Moquet et al 2001;Anderson et al 2002Anderson et al , 2003Barquinero et al 2004;Anderson et al 2007;Tawn et al 2007Tawn et al , 2008Curwen et al 2012). A densely ionizing a-particle will only intersect a small fraction of the cell volume and the deposition of energy and resulting DNA damage will be localized along the particle track, resulting in multiple rearrangements.…”
Section: Introductionmentioning
confidence: 97%
“…However, more detailed analyses revealed that most insertions and inversions were part of complex unstable aberrations, and therefore very few would be transmissible (Barquinero et al 2004;Tawn et al 2007Tawn et al , 2008Curwen et al 2012). Nevertheless, the application of multi-coloured FISH (mFISH) has shown that, whilst the majority of aparticle-irradiated cells will suffer complex non-transmissible chromosome damage, a significant proportion survive with simple exchanges, in particular translocations, that can be passed on to descendant cells (Anderson et al 2005;Curwen et al 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Hybridisation, post-hybridisation washes and signal detection conditions were carried out following the method described by Tawn et al . 5 …”
Section: Methodsmentioning
confidence: 99%
“…However, the ratio of complex to simple interchanges (C ratio) was found higher for high LET radiation as compared to X-rays and the authors suggested that the C ratio should therefore be considered for biophysical modeling studies. Tawn et al [129] demonstrated a much higher induction of intrachromosomal changes by α-particles relative to rays. Using sister chromatid differentiation technique, Cartwright et al [130] reported the dependence of both radiation quality and chromatin structure on inversion frequencies in CHO cells.…”
Section: Multicolor Band For Detection Of Intrachromosomal Changesmentioning
confidence: 97%